NARASI KRIMINALITAS DAN KISAH PERCINTAAN DALAM NOVEL TJERITA NONA GAN JAN NIO ATAWA PERTJINTA’AN DALEM RASIA (1914) KARYA TAN BOEN KIM: KAJIAN PASCAKOLONIAL - Susanto, Dwi (Sunan Kalijaga State Islamic University Yogyakarta, 2019)
Crime and romance were common themes in Chinese Indonesian literature during the colonial era. Although this literary genre falls into a subgenre, it aesthetically provides a covert narration of intermixing worlds: East and West. This paper examines the practices of liminality and identity construction in Tan Boen Kim’s Tjerita Nona Gan Jan Nio atawa Pertjinta’an dalem Rasia (1914). The construction of identity in liminal spaces in the novel is interpreted through postcolonial lens, especially based on the concepts of hybridity and ambivalence. The material object of this study is the novel, and the formal object is the meeting of the subjects in the liminal space. The data are collected from the content of the text, the topic, the social context, and other relevant sources. The interpretation technique is performed through deconstructive reading and circular reading between the text and the social context. Based on the analysis, it is found that Tan Boen Kim preserved the moral traditions on the one hand but promoted liberalism on the other hand. It is also found that the author’s attitude in “moderation” (moderate-tradition) position is based upon his choices of cultural construction which is between moderate and tradition—thus making his strategy characterized by ambivalence.